The architecture of EGFR’s basal complexes reveals autoinhibition mechanisms in dimers and oligomers - Laura C. Zanetti-Domingues (Nature Portfolio, 2018)
To prevent ligand-independent dimerisation the epidermal growth factor receptor (EGFR) is autoinhibited by an extracellular dimer interaction. Here, the authors use several imaging technologies and simulations to provide structural insights on the inactive species and on how intracellular mutations circumvent the autoinhibition of the basal state.